Effectiveness of low-frequency vibration recovery method on blood lactate removal, muscle contractile properties and on time to exhaustion during cycling at VO2max power output - Carrasco, L.; Sañudo, B.; de Hoyo, M.; Pradas, F.; da Silva, M. E. (European Journal of Applied Physiology, 2011)
The aim of the study was to determine the effectiveness of low-frequency vibration recovery (LFV-rec) on blood lactate removal, muscle contractile properties, and on time to exhaustion during cycling at maximal oxygen uptake power output (pVO2max). Twelve active males carried out three experimental sessions. In session 1, participant`s maximal oxygen uptake (VO2max) and pVO2max were determined, and in sessions 2 and 3, the participants performed a fatiguing exercise (2 min of cycling at pVO2max) and then a 15 min recovery period using one of two different methods: LFV-rec which consisted on sitting with feet on the vibratory platform (20 Hz; 4 mm) and passive recovery (P-rec), sitting without vibration stimulus. After that, participants performed an all-out exercise test on cycle ergometer at pVO2max. In the recovery period, variables such as heart rate (HR), blood lactate concentration [Lac], and tensiomyographic parameters (D m: maximal radial displacement; T s: time of contraction maintenance, and T r: relaxation time) were measured. In an all-out exercise test, mean time to exhaustion (TTE), total distance covered (TD), mean cycling velocity (V m), and maximal HR (HRmax) were also assessed. The results showed no effect of recovery strategy on any of the assessed variables; nevertheless, higher values, although not significant, were observed in TTE, TD, and V m after LFV-rec intervention. In conclusion, LFV-rec strategy applied during 15 min after short and intense exercise does not seem to be effective on blood lactate removal, muscle contractile properties, and on time to exhaustion during cycling at pVO2max.